THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION AND COMPETITIVE ADVANTAGE ON PERFORMANCE - Rika Rahmayuni; Yulia Hendri Yeni; Syafrizal (Halu Oleo University, 2024)
This research aims to examine the influence of entrepreneurial orientation, competitive advantage and on the performance of culinary MSEs in West Sumatra. This research helps MSEs to apply the results of this research in increasing the competitive advantage and performance of MSEs. The research method used is quantitative. The population in this research are owners or managers of culinary MSEs in West Sumatra. The sample used was 160 samples using a non-probability sampling method and using a purposive sampling technique. This research uses PLS-SEM with the help of SmartPLS software version 4.0. The research results show that entrepreneurial orientation has a positive and significant effect on the performance of culinary MSEs in West Sumatra. Entrepreneurial orientation has a positive and significant effect on competitive advantage. Competitive advantage has a positive and significant effect on the performance and entrepreneurial orientation influences performance through the competitive advantage of culinary MSEs in West Sumatra.